Construction of metallo-triangles with cis-TPE motifs and fluorescence properties. Issue 99 (25th November 2022) - Shi, Junjuan; Li, Meng; Su, Haoyue; Bai, Qixia; Han, Ningxu; Hao, Xin-Qi; Fang, Fang; Zhang, Zhe; Wang, Pingshan; Ma, Benhua; Wang, Ming
Abstract : Two metallo-triangles SA and SB with cis -TPE motifs were constructed and their fluorescence properties were explored. Compared with dilute solution, both triangles SA and SB exhibited significant AIE behavior in the aggregated states. Abstract : Two metallo-triangles, SA and SB, with cis -TPE motifs were constructed, and their fluorescence properties were explored. Compared with the dilute solution, both triangles SA and SB exhibited significant AIE behavior in the aggregated states. Moreover, the shorter version SA showed higher quantum yields than SB in the aggregated states.